The mitochondrial genome of Angiostrongylus mackerrasae as a basis for molecular, epidemiological and population genetic studies - Mahdis Aghazadeh; Rebecca J. Traub; Namitha Mohandas; Kieran V. Aland; Simon A. Reid; James S. McCarthy; Malcolm K. Jones (Parasites & Vectors, 2015)
Abstract Background Angiostrongylus mackerrasae is a metastrongyloid nematode endemic to Australia, where it infects the native bush rat, Rattus fuscipes. This lungworm has an identical life cycle to that of Angiostrongylus cantonensis, a leading cause of eosinophilic meningitis in humans. The ability of A. mackerrasae to infect non-rodent hosts, specifically the black flying fox, raises concerns as to its zoonotic potential. To date, data on the taxonomy, epidemiology and population genetics of A. mackerrasae are unknown. Here, we describe the mitochondrial (mt) genome of A. mackerrasae with the aim of starting to address these knowledge gaps. Methods The complete mitochondrial (mt) genome of A. mackerrasae was amplified from a single morphologically identified adult worm, by long-PCR in two overlapping amplicons (8 kb and 10 kb). The amplicons were sequenced using the MiSeq Illumina platform and annotated using an in-house pipeline. Amino acid sequences inferred from individual protein coding genes of the mt genomes were concatenated and then subjected to phylogenetic analysis using Bayesian inference. Results The mt genome of A. mackerrasae is 13,640 bp in size and contains 12 protein coding genes (cox1-3, nad1-6, nad4L, atp6 and cob), and two ribosomal RNA (rRNA) and 22 transfer RNA (tRNA) genes. Conclusions The mt genome of A. mackerrasae has similar characteristics to those of other Angiostrongylus species. Sequence comparisons reveal that A. mackerrasae is closely related to A. cantonensis and the two sibling species may have recently diverged compared with all other species in the genus with a highly specific host selection. This mt genome will provide a source of genetic markers for explorations of the epidemiology, biology and population genetics of A. mackerrasae.